Particulates Matter: The Influence of Cumulative Local Air Pollution Exposure on Sixth-Grade Academic Achievement in California - Robert W Wassmer; Michael D Turgeon (Environmental Health Insights)
We examine the influence of exposure to fine particulate matter (PM 2.5) in ambient air over the previous 6 years on the average standardized test score performance in math, English language arts (ELA), and overall for sixth graders at a sample of California public school districts from 2015 through 2018. Public health research suggests that children exposed to localized air pollution may suffer from cognitive impairment during testing or chronic conditions such as asthma that could influence their academic performance. After controlling for the appropriate confounding variables, our findings indicate that a 1-unit increase (or an equivalent one-third increase in the standard deviation) in the average amount of particulate matter observed over the past 6 years in a school district reduces the average standardized test score by about 4%. In addition, a typical student in a California school district in the two highest quintiles of PM 2.5 exposure (controlling for other causal factors) exhibits standardized test scores closer to the fifth-grade equivalency level than the sixth. These results support the benefits of indoor air pollution mitigation as a likely cost-effective intervention to improve student academic success in primary school.